Estimating optimal sample size for tardigrade morphometry. (December 2016) - Stec, Daniel; Gąsiorek, Piotr; Morek, Witold; Kosztyła, Paulina; Zawierucha, Krzysztof; Michno, Klaudia; Kaczmarek, Łukasz; Prokop, Zofia M.; Michalczyk, Łukasz
Abstract : Tardigrade taxonomy is based largely on classical methodology, with morphological and morphometric traits being most often the sole basis for species delineation and identification. However, despite over 1200 described tardigrade species, so far there have been no studies estimating the sample size that would allow confident interpretation of dimensions of taxonomically important characters. We defined such optimal sample size as a minimal number of structures that need to be measured in order to result in a mean and a range that are not significantly different from the global (population) values. We estimated the optimal sample size by employing a randomized sampling approach to an extensive data set of more than 28 000 morphometric measurements for over 2300 individuals of six tardigrade species representing four major families (Milnesiidae, Hypsibiidae, Isohypsibiidae and Macrobiotidae) of the two eutardigrade orders, Apochela and Parachela. We found that the optimal sample size for the accurate estimation of trait means varied between 6 and 40, with 19 measurements being the overall average. In the case of trait ranges, sample size was much higher (26–413; 130 on average). Given that the range can be covered by measuring the smallest and largest specimens, we suggest that for accurate mean estimation at least 20 measurements ought to be taken, although 30 should be aimed at. We discuss our findings in light of the current practice in tardigrade taxonomy and provide suggestions that could improve the quality of tardigrade species descriptions.